Cyclosporine Monotherapy in Pediatric Patients With Non-severe Aplastic Anemia: A Retrospective Analysis - Li, Hongmin; Fu, Lingling; Yang, Bixi; Chen, Hui; Ma, Jie; Wu, Runhui (Frontiers in Medicine, 2022)
Objective: The study aimed to investigate the efficacy of Cyclosporine (CsA) monotherapy for pediatric NSAA. Methods: Clinical data of children with NSAA who had been treated with CsA monotherapy at the outpatient department of Beijing Children's Hospital, Capital Medical University, National Children's Medical Center from January 2017 to March 2021 was collected retrospectively. Patients who had been treated less than 1 years until the end of follow-up were excluded. Transfusion-independent NSAA was further divided into moderate NSAA and mild NSAA according to the degree of cytopenia. Results: A total of 95 pediatric patients with NSAA were enrolled in this study with 49(51.6%) patients confirmed as mild NSAA, 38(40%) as moderate NSAA and 8(8.4%) as transfusion-dependent NSAA. The median treatment time of CsA was 22(12-44) months. The overall response rate(ORR) was 57.9%, with 30.5% CR and 27.4% PR. Unexpectedly, patients with mild NSAA acquired lowest ORR (46.9%), then patients with moderate NSAA (63.2%), while 8 patients who were transfusion-dependent all had an active response to CsA. The granulocyte and megakaryocyte response was 46.9% and 55.8% respectively, while the erythrocyte response rate was as low as 22.5%. Univariate analyses revealed that patients with lower platelet count and higher interleukin 10 level predict an active response to CsA while higher level of fetal hemoglobin (HbF) tended to be a negative factor. Paired comparison found that the percentage of Treg cells in CD4+ T cells was decreased after one year's treatment of CsA(6.78 ±2.72 vs 5.23±2.06，P=0.001),both in responders and non-responders. The degree of decline in Treg cells between two distinctive response groups had no significant difference（P>0.05). With a median follow-up time of 22 months, 10.9% of responders relapsed and maintained NSAA while 27.5% of non-responders progressed to SAA or became transfusion-dependent. The overall progression rate was 11.6%. Conclusion: CsA monotherapy had heterogeneous effects in the treatment of children NSAA.Patients with lower platelet count and higher interleukin 10 level predicted an active response to CsA. While higher level of fetal hemoglobin (HbF) tended to be a negative factor. The percentage of Treg cells in CD4+ T cells was decreased broadly after treatment.